Thermodynamic modeling adsorption behavior of a well-known gelation crosslinker on sandstone rocks - Yang Yue; Ayat Hussein Adhab; Dharmesh Sur; Soumya V. Menon; Abhayveer Singh; S. Supriya; Shakti Bedanta Mishra; Deepak Nathiya; Morug Salih Mahdi; Aseel Salah Mansoor; Usama Kadem Radi; Nasr Saadoun Abd; et al. (Scientific Reports)
Abstract This study examines the adsorption behavior of hydroquinone (HQ) on quartz and sandstone surfaces under various thermal conditions. Adsorption isotherms, including the Langmuir, Freundlich, Temkin, and linear models, were applied to experimental data to predict adsorption capacity and understand underlying mechanisms. Among these, the Langmuir model, characterized by high R2 (0.999), demonstrated superior accuracy, confirming monolayer adsorption on a homogeneous surface, with a maximum adsorption capacity (qo) of 47.1 mg/g at 25 °C. Thermodynamic analysis revealed the exothermic nature of adsorption, with negative Gibbs free energy (ΔG) values across all tested temperatures, indicating spontaneous behavior. However, the adsorption capacity decreased significantly with temperature, from 47.1 mg/g at 25 °C to 27.1 mg/g at 80 °C, due to increased molecular motion and reduced HQ-quartz surface interactions. Furthermore, adsorption experiments in porous sandstone media showed lower adsorption capacities, attributed to the heterogeneity of the sandstone structure and restricted accessibility of active sites, with values decreasing from 24 mg/g at 25 °C to 14 mg/g at 95 °C. Thermodynamic constants such as enthalpy (ΔH = − 8,018 J/mol) and entropy (ΔS = 6.12 J/mol·K) emphasize the temperature dependence of the process. These findings provide crucial insights for designing efficient chemical injection strategies in subsurface environments, bridging the gap between laboratory conditions and real-world applications in reservoir engineering.